Pendampingan Sertifikasi Halal bagi Pelaku Industri Kecil Menengah (IKM) di Desa Banyu Sangka Tanjung Bumi Bangkalan Madura - Sunariyah, Anik; Mawardi, Imam; Rohman, Abdur (Santri : Journal of Student Engagement, 2024)
Banyusangka is one of the villages in Tanjung Bumi kecataman, Regency of Bangkalan. It has unique characteristics compared to other villages. It is known for its culinary treats, such as soto kotal (tongkol), gherreng (ikan asin), acan (pasta ikan asin), rujak ontal, pat ceppret, and pek empek fish, which the community produces as a middle-class small business. Entrepreneurs and people who have products are required to register their products in order to receive halal certificates, as stipulated by Law No. 33 of 2014 concerning guarantees of halal products. The purpose of this community service is to inform small and medium industries (IKM) in Banyusangka village about the standards that must be met by IKM to obtain halal certificates, educate IKM in Banyusangka village about the importance of awareness and the benefits of halal certificates, and provide information and instructions on how to apply for halal certificates for IKM in Banyusangka village.  The PAR method emphasizes the importance of collective social processes to achieve activity goals and the results of research related to halal product certification assistance, including assistance with SIHALAL account registration for business actors, including completing IKM data at http://ptps.halal.go.id and facility registration data through the JPH Halal Center UTM, and the conclusion of the service is that it can provide import.